APOE and the Association of Fatty Acids With the Risk of Stroke, Coronary Heart Disease, and Mortality. Issue 12 (December 2018) - Satizabal, Claudia L.; Samieri, Cécilia; Davis-Plourde, Kendra L.; Voetsch, Barbara; Aparicio, Hugo J.; Pase, Matthew P.; Romero, José Rafael; Helmer, Catherine; Vasan, Ramachandran S.; Kase, Carlos S.; Debette, Stéphanie; Beiser, Alexa S.; et al.
Abstract : Background and Purpose—: The role of dietary fat on cardiovascular health and mortality remains under debate. Because the APOE is central to the transport and metabolism of lipids, we examined associations between plasma fatty acids and the risk of stroke, coronary heart disease, and mortality by APOE-ε4 genotype. Methods—: We included 943 FHS (Framingham Heart Study) and 1406 3C (Three-City) Bordeaux Study participants. Plasma docosahexaenoic, linoleic, arachidonic, and palmitic fatty acids were measured at baseline by gas chromatography. All-cause stroke, ischemic stroke, coronary heart disease, and all-cause mortality events were identified prospectively using standardized protocols. Each cohort used Cox models to separately relate fatty acid levels to the risk of developing each event during ⩽10 years of follow-up adjusting for potential confounders and stratifying by APOE genotype (ε4 carriers versus noncarriers). We then meta-analyzed summary statistics using random-effects models. Results—: On average, participants had a mean age of 74 years, 61% were women, and 21% (n=483) were APOE-ε4 carriers. Meta-analysis results showed that, only among APOE-ε4 carriers, every SD unit increase in linoleic acid was associated with a reduced risk of all-cause stroke (hazard ratio [HR], 0.54 [95% CI, 0.38–0.78]), ischemic stroke (HR, 0.48 [95% CI, 0.33–0.71]), and all-cause mortality (HR, 0.70 [95% CI, 0.57–0.85]). In contrast, every SD unit increase in palmitic acid was related to an increased risk of all-cause stroke (HR, 1.58 [95% CI, 1.16–2.17]), ischemic stroke (HR, 1.76 [95% CI, 1.26–2.45]), and coronary heart disease (HR, 1.48 [95% CI, 1.09–2.01]), also in APOE-ε4 carriers only. Results for docosahexaenoic acid and arachidonic acid were heterogeneous between cohorts. Conclusions—: These exploratory results suggest that APOE-ε4 carriers may be more susceptible to the beneficial or adverse impact of fatty acids on cardiovascular disease and mortality. In this subgroup, higher linoleic acid was protective for stroke and mortality, whereas palmitic acid was a risk factor for stroke and coronary heart disease. The mechanisms underlying these novel findings warrant further investigation. Abstract : Supplemental Digital Content is available in the text.